Reader's Digest Crafts & Hobbies - Susan Chace; Lilla Pennant; Daniel Weiss (USA Reader's Digest Association, 1979)
Presents instructions for many different crafts and hobbies, including woodworking, macrame, origami, drawing and many more
About this book -- Creating a home workshop -- Leatherworking -- Macrame -- Decoupage -- Candlemaking -- Papier-mache -- Basketry -- Spinning and dyeing -- Weaving -- Batik and tie-dyeing -- Stained glass -- String art -- Origami -- Pottery -- Quiltmaking -- Modeling, moldmaking, and casting -- Sculpture -- Drawing -- Color and design -- Painting -- Printmaking -- Printing on fabric -- Stenciling -- Collage -- Wood sculpture -- Metalworking -- Indoor gardening -- Drying and preserving flowers -- Mosaics -- Lapidary -- Jewelry -- Enameling -- Woodworking -- Picture framing -- Preserving fruit -- Breads from around the world -- Winemaking -- Restoring furniture -- Bookbinding
Includes index
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; Handicraft; Hobbies; General